2020
DOI: 10.3390/cells9102275
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Maturation of iPSC-CMs Leads to the Enhanced Compartmentation of β2AR-cAMP Signalling

Abstract: The ability to differentiate induced-pluripotent stem cells into cardiomyocytes (iPSC-CMs) has opened up novel avenues for potential cardiac therapies. However, iPSC-CMs exhibit a range of somewhat immature functional properties. This study explored the development of the beta-adrenergic receptor (βAR) pathway, which is crucial in regulating contraction and signifying the health and maturity of myocytes. We explored the compartmentation of β2AR-signalling and phosphodiesterases (PDEs) in caveolae, as functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…It shall be further noted that the fully differentiated hiPSC-CMs, even at day ~100, do not display a complete T-Tubular network, leaving open the question if the β 2 -AR, that in this work we observed on the basolateral membrane, would eventually segregate in these compartments [ 13 ]. Our observation of higher relative β 2 -AR expression levels in hiPSC-CMs appears to be in line with what was previously reported in at least three works [ 8 , 9 , 10 ]. However, we shall mention here that in recent measurements in hiPSC-derived engineered heart tissue, higher levels of β 1 -AR were observed throughout (private communication and [ 25 ]).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It shall be further noted that the fully differentiated hiPSC-CMs, even at day ~100, do not display a complete T-Tubular network, leaving open the question if the β 2 -AR, that in this work we observed on the basolateral membrane, would eventually segregate in these compartments [ 13 ]. Our observation of higher relative β 2 -AR expression levels in hiPSC-CMs appears to be in line with what was previously reported in at least three works [ 8 , 9 , 10 ]. However, we shall mention here that in recent measurements in hiPSC-derived engineered heart tissue, higher levels of β 1 -AR were observed throughout (private communication and [ 25 ]).…”
Section: Discussionsupporting
confidence: 93%
“…Wu et al observed mRNA levels and effects on the contractility of β-AR expression in differentiating hiPSC, in a model of dilated cardiomyopathy [ 8 ]. Jung et al studied adrenoreceptor mRNA and total protein levels within the context of functional remodeling [ 9 ], while Hasan et al examined how receptor-specific cAMP signaling evolves throughout hiPSC differentiation towards CMs [ 10 ]. Kondrashov et al studied the temporal dynamics of β 2 -AR expression in CRISPRed hiPSC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It shall be further noted that the fully CM-differentiated hiPSCs, even at day ~100, do not display a complete T-Tubular network, leaving open the question if the β2-AR, that in this work we observed on the basolateral membrane, would eventually segregate in these compartments [13]. Our observation of higher relative β2-AR expression levels in hiPSC-CMs appears to be in line with what was previously reported in at least three works [6,9,10]. Although, we shall mention here, that in recent measurements in hiPSC-derived engineered heart tissue, higher levels of β1-AR were observed throughout (private communication and [23]).…”
Section: Discussionsupporting
confidence: 92%
“…Wu et al observed mRNA levels and effects on contractility of β-AR expression in differentiating hiPSC, in a model of dilated cardiomyopathy [6]. Jung et al studied adrenoreceptor mRNA levels within the context of functional remodelling [9], while Hasan et al monitored how receptor-specific cAMP signaling evolves throughout hiPSC differentiation towards CMs [10]. Kondrashov et al studied the temporal dynamics of β 2 -AR expression in CRISPRed hiPSC [11].…”
Section: Introductionmentioning
confidence: 99%
“…The low level of cAMP may for example derive from the high activity of phosphodiesterases (PDEs). The role of PDEs and in particular PDE3 and PDE4 in hiPS-CM has been recently shown in various works in which their inhibition resulted in the increase of basal cAMP level [22,25,26]. We may speculate that the low level of cAMP and high PDE activity may also explain the significantly slower time constant of the isoproterenol-mediated rate acceleration (7.6 ± 1.0 s) than the time constant of the rate slowing due to muscarinic receptors activation (3.4 ± 0.8 s).…”
Section: Discussionmentioning
confidence: 98%